Lee and Mitchell's unfolding model of employee turnover - a theoretical assessment - Kevin Morrell; John Loan-Clarke; Adrian Wilkinson (2001)
This paper offers a critique of the ‘unfolding’ model of employee turnover (Lee, Mitchell, Holtom, Daniel & Hill 1999), and is intended to contribute to debate on the theoretical and operational merits of this alternate approach to analyzing turnover. The critique explores the model’s conceptual framework and theoretical contribution, as well as offering thoughts on logistical and operational issues.